A simple route for additive manufacturing of 316L stainless steel via Fused Filament Fabrication. (July 2021) - Sadaf, M.; Bragaglia, M.; Nanni, F.
Graphical abstract: Highlights: Feedstock made of 65 % volume fraction 361L stainless steel with 35 % LDPE was developed. 3D printing of metal feedstock was carried out by fused filament fabrication (FFF). 3D printed parts were thermally debound and sintered into 91–93% densified steel parts. Abstract: The low-cost material extrusion (MEX) additive manufacturing technology can offer an economical alternative to manufacture metal parts with complex geometry over traditional manufacturing or the more expensive powder bed fusion (PBF) techniques. In this work, a feedstock made of 316L stainless steel powder (65 % by volume) and a single component binder (LDPE) system was developed. The use of a single binder rather than two or more components, commonly used in metal MEX, introduces a novel and more sustainable solution in terms of costs and less use of chemicals. The rheology and processability of the feedstocks were studied, and samples were 3D printed. Debinding and sintering under a hydrogen atmosphere at 1380 °C were performed, and the resulting metallic parts have been characterized by a mechanical and microstructural point of view. The results show a sintered steel having 93 % of the theoretical density and an austenitic phase confirming that the post-processing under reductive atmosphere protected the samples from oxidation and other contamination. The sintered 3D parts show a grain size of ∼ 45 μm, a yield point of 250 MPa, a tensile strength of 520 MPa, and a Vickers microhardness of 285 HV typical of annealed steel.